Signalment and C-reactive protein values in dogs with immune-mediated polyarthritis and steroid responsive meningitis arteritis - Indzhova, Viktoriya; Czopowicz, Michał; Kilpatrick, Scott; Gutierrez-Quintana, Rodrigo; Brocal, Josep (Frontiers in Veterinary Science, 2023)
This retrospective multicentric study aims to evaluate the ability of CRP concentration to differentiate between dogs diagnosed with IMPA and SRMA. C-reactive protein (CRP) is a marker of inflammation widely used in two of the most commonly diagnosed immune-mediated diseases in dogs – immune-mediated polyarthritis (IMPA) and steroid responsive meningitis arteritis (SRMA). Data collected from medical records of 167 client-owned dogs included age, breed, gender, neuter status, body weight, body temperature, CRP concentration, month and season of diagnosis. CRP was measured quantitatively in 142 dogs (84%) and semi-quantitatively in 27 dogs (16%). SRMA was diagnosed significantly more often in dogs < 12 months old whereas IMPA in dogs ≥ 12 months old (P<0.001). Dogs diagnosed with SRMA had higher CRP concentration than dogs diagnosed with IMPA (P=0.02). This difference was influenced by the dog’s age – when a dog was < 12 months old, a higher CRP concentration indicated IMPA (P=0.02), whereas when a dog was ≥ 12 months old, a higher CRP concentration indicated SRMA (P=0.02). CRP concentration as a sole diagnostic modality showed only fair discriminatory potential to differentiate between SRMA and IMPA (area under ROC curve close to 0.7). CRP concentration varied depending on patient age and definitive diagnosis. It may play some role in differentiating between SRMA and IMPA but should not be used as the sole diagnostic modality, given it has been demonstrated to only have fair discriminatory potential.